Application of KKL model in studying of nanofluid heat transfer between two rotary tubes. (September 2019) - Alsagri, Ali Sulaiman; Moradi, Rasoul
Abstract: In the present paper, the Koo–Kleinstreuer–Li (KKL) approach is used to study the flow of nanofluid between two circular tubes in occurrence of Lorentz force. Solving the corresponding ODEs is done by means of homotopy perturbation method (HPM). The effect of different active parameters, i.e. Eckert number ( Ec ), aspect ratio ( η ), magnetic number ( Ha ), and Reynolds number ( Re ) is investigated. Findings indicate that the gradient of temperature augments as Ha, Ec and η rises. However, growth of Re leads to a reduction in temperature gradient. Furthermore, increasing the Lorentz forces results in a reduction in velocity while augmentation of Re enhances the speed.